Immunohistochemical analysis of intrasulcal hematoma due to cerebral amyloid angiopathy in a brain‐dead patient. Issue 4 (6th June 2018) - Takeda, Shigeki; Onda, Kiyoshi; Yoshida, Yuichi
Abstract : Neuropathological examinations of the brain in cases of brain death are usually insufficient because of autolysis. We examined a case of sporadic‐type cerebral amyloid angiopathy‐related hemorrhage (sCAA‐H) in a 74‐year‐old Japanese woman who had been clinically established as brain dead 7 days before cardiac arrest. The brain was macerated, and a huge hematoma was evident in the right parieto‐occipital region. Ordinary neuropathological examination was unable to clarify where the hematoma was located in the brain parenchyma or the subarachnoid space (SAS). Immunohistochemistry for amyloid‐β (Aβ) and synaptophysin revealed that: (i) the hematoma affected the cerebral sulcus, cerebral cortex (CC) and subcortical white matter; (ii) the CC was destroyed at the depth of the cerebral sulcus; (iii) in three 6‐μm‐thick sections, ruptured Aβ‐positive vessels were seen only in the intrasulcal hematoma and not in the CC or intracerebral hematoma; and (iv) in the CC adjacent to the intrasulcal hematoma, a few macrophages were observed, indicating a fresh infarct of the CC. These findings indicate that sCAA‐H occurred first in the cerebral sulcus due to rupture of multiple meningeal vessels, as had been documented in our previous reports. The present study shows that even in an autolytic dead brain, immunohistochemistry is more useful than ordinary staining methods. Other than double‐barreled vessels, several vascular changes such as fibrinoid degeneration, segmental dilatation (so‐called micro‐aneurysmal dilatation), and hyalinous onion‐like change of the intima were seen in the intrasulcal hematoma, SAS and CC. Interestingly these vascular changes were not observed in the ruptured Aβ‐positive vessels. More detailed studies will be needed to examine the correlation between these vascular changes and vessel rupture.